2007
DOI: 10.1093/glycob/cwm009
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1/CD147 association is essential for cyclophilin B-induced activation of p44/42 mitogen-activated protein kinases and promotion of cell adhesion and chemotaxis

Abstract: Many of the biological functions attributed to cell surface proteoglycans are dependent on the interaction with extracellular mediators through their heparan sulphate (HS) moieties and the participation of their core proteins in signaling events. A class of recently identified inflammatory mediators is secreted cyclophilins, which are mostly known as cyclosporin A-binding proteins. We previously demonstrated that cyclophilin B (CyPB) triggers chemotaxis and integrin-mediated adhesion of T lymphocytes mainly of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 53 publications
8
88
0
Order By: Relevance
“…This may explain why CyPB was unable to induce the expression of TNF-a and possibly other proinflammatory cytokines and chemokines that have NF-kB and c-Jun binding sites in their promoters in a similar configuration to the TNF-a promoter. Importantly, other studies also reported that CyPA did not induce the activation of p38 MAPK and JNK pathways in responsive cells (15,31,37). Hence, our current work extends previous studies to demonstrate that, besides stimulating monocytes/macrophages chemotaxis, extracellular CyPA and CyPB may induce a low production of specific cytokines (e.g., IL-6) without leading to a generalized production of proinflammatory mediators.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This may explain why CyPB was unable to induce the expression of TNF-a and possibly other proinflammatory cytokines and chemokines that have NF-kB and c-Jun binding sites in their promoters in a similar configuration to the TNF-a promoter. Importantly, other studies also reported that CyPA did not induce the activation of p38 MAPK and JNK pathways in responsive cells (15,31,37). Hence, our current work extends previous studies to demonstrate that, besides stimulating monocytes/macrophages chemotaxis, extracellular CyPA and CyPB may induce a low production of specific cytokines (e.g., IL-6) without leading to a generalized production of proinflammatory mediators.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, we demonstrated that CyPB is a chemoattractant factor for human peripheral blood CD4 + T lymphocytes via a mechanism dependent on the activation of p44/p42 MAPK (20,31). In the current study, we confirmed these findings with human macrophages and extended them to show that CyPB also activates the NF-kB pathway ( Fig.…”
Section: Cypb Induces Signaling Events and Chemotaxis On Human Primarsupporting
confidence: 85%
“…Our studies identified CD147 as an essential component of the cell-surface signaling receptor to CypA and CypB [10;11;13]. This notion has been supported in a number of subsequent publications [14][15][16]. CypA is incorporated into HIV-1 particles during virus morphogenesis through a specific interaction with the CA domain of the Gag precursor polyprotein [17][18][19][20] and plays an essential role in the early steps of the HIV-1 life cycle [21;22].…”
Section: Introductionsupporting
confidence: 71%
“…The mechanism of signaling from CD147 might involve two different signal transduction pathways: one mediated by the cytoplasmic tail of the protein and the other -by CD147-associated transmembrane proteins, such as integrins or syndecans, as suggested previously [14;29]. Indeed, downregulation of syndecan-1 has been shown to prevent CypB-induced ERK activation [14]. It remains to be determined whether signaling events can really be transduced through the cytoplasmic tail of CD147.…”
Section: Cytoplasmic Domain Of Cd147 Is Necessary For Enhancement Of mentioning
confidence: 84%
“…Thus, in the absence of MMP7, neutrophils would retain ligation to the negative signal. This model implies that MMP7 shedding of syndecan-1 could affect the activity of the putative repressor, and, indeed, shedding of syndecans does affect the activation state of other receptors, such as integrins (11,(41)(42)(43)(44)(45). Although this possible mechanism appears attractive, the specific means by which epithelial cells can constrain neutrophil activation remain to be determined.…”
Section: Discussionmentioning
confidence: 99%